3(10-6)(3-7)=

Simple and best practice solution for 3(10-6)(3-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(10-6)(3-7)= equation:


Simplifying
3(10 + -6)(3 + -7) = 0

Combine like terms: 10 + -6 = 4
3(4)(3 + -7) = 0

Combine like terms: 3 + -7 = -4
3 * 4(-4) = 0

Multiply 3 * 4
12 * -4 = 0

Multiply 12 * -4
-48 = 0

Solving
-48 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 55m-139m-64m= | | 8x^6/6x^3 | | ln(x-3)=1.4 | | x-9(2/3x-6)=30 | | 1/2z=9/4 | | -5/13x=-8 | | 5m-139m-64m= | | 10m^3n^3-2mn^2+14mn= | | x+y-3z=-7 | | -9+8x=7x+15 | | 5(x+8)-6=44 | | 8x^2-28x+2x-7=.5 | | 5849=3.14x*81 | | 11w=132 | | -30=x+12 | | 17.8-(-4.006)-22= | | 4(-7e+9)+6=82 | | 46=(-6t)-8 | | (16x^5-x)(4x^2-9)=0 | | 4+(19-42)2= | | 2n+n=57 | | 12x(3x-2+5y)-4(5x-3y+2)-5y= | | r*25=6 | | 4=225 | | n/2-4=18 | | 2m^2+7m-1=-6 | | 3x/27=8/2x | | 5n+6+6n=30 | | 3(n-8)=5 | | 3p^2q^2+6pq+p= | | 5p-7q=-1 | | 3x^4-14x^2-5=0 |

Equations solver categories